Membangun Budaya Literasi Bagi Pegawai Negeri Sipil Dalam Usaha Bela Negara - Yudi Kresnasurya (Cendekia Niaga, 2020)
This paper discusses the importance of building a culture of literacy for civil servants in the defense of the state. Defending of country is the right and obligation of every citizen, and can be done in accordance with the profession. The approach used in this paper is qualitative. The data is taken through a literature review (literature study). This study reinforces some of the results of previous research in the importance of building a culture of literacy, in this case for state defense efforts by civil servants.